Heavy Metals in Baby Food: What Providers and Parents Need to Know. Issue 2 (March 2020) - Beal, Judy A.
Abstract : A recent study found that 95% of baby foods are contaminated with heavy metals. Our pediatric nursing expert, Dr. Beal, explains the details of the 2019 study from Healthy Babies Bright Futures and how nurses can advise parents to avoid the most commonly contaminated foods.